2021
DOI: 10.1108/jsocm-05-2020-0088
|View full text |Cite
|
Sign up to set email alerts
|

The role of norms in predicting waste sorting behavior

Abstract: Purpose This study aims to examine the role of personal and subjective norms in predicting waste sorting, an increasingly relevant pro-environmental behavior. Design/methodology/approach This study obtained data from a sample of 300 respondents from three Indonesian cities. Purposive sampling was employed to obtain information from specific segments of Indonesian population. The analysis consisted of a two-stage procedure including confirmatory factor analysis and covariance-based structural equation modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 78 publications
2
23
0
Order By: Relevance
“…Personal norm represents a moral duty to engage in a particular conduct or refrain from doing so, AC is defined as people's understanding of how pro-social behavior benefits others or their estimations of other things, and the AR shows how responsible people feel about the effects of their pro-social behavior. NAM is regarded as the most influential theory in explanation of proenvironmental decision-making process and behavior (Steg and Nordlund, 2018;Esfandiar et al, 2019Esfandiar et al, , 2022Han, 2021;Mikuła et al, 2021;O'Connor and Assaker, 2021;Gao et al, 2022), households' waste separation (Goh et al, 2022), purchase food (Faletar et al, 2021;Lafontaine et al, 2021;Yang et al, 2021;Le and Nguyen, 2022), waste separation behavior (Esfandiar et al, 2021;Setiawan et al, 2021;Shen et al, 2022), these studies have shown that AR, AC positively affected PN, and AR can be triggered by AC. Accordingly, this research proposes the hypothesis as follows:…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Personal norm represents a moral duty to engage in a particular conduct or refrain from doing so, AC is defined as people's understanding of how pro-social behavior benefits others or their estimations of other things, and the AR shows how responsible people feel about the effects of their pro-social behavior. NAM is regarded as the most influential theory in explanation of proenvironmental decision-making process and behavior (Steg and Nordlund, 2018;Esfandiar et al, 2019Esfandiar et al, , 2022Han, 2021;Mikuła et al, 2021;O'Connor and Assaker, 2021;Gao et al, 2022), households' waste separation (Goh et al, 2022), purchase food (Faletar et al, 2021;Lafontaine et al, 2021;Yang et al, 2021;Le and Nguyen, 2022), waste separation behavior (Esfandiar et al, 2021;Setiawan et al, 2021;Shen et al, 2022), these studies have shown that AR, AC positively affected PN, and AR can be triggered by AC. Accordingly, this research proposes the hypothesis as follows:…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Authority Regulation Number 76/POJK.07/2017, is the availability of access to various financial institutions, products, and services by the needs and capabilities of the community in order to improve the welfare of the community [12]. Furthermore, financial inclusion, according to SNLKI (2017), is "access to financial products and services that are useful and affordable in meeting the needs of the community and their businesses in terms of transactions, payments, credit savings, and insurance that are used responsibly and sustainably".…”
Section: Financial Inclusion Based On the Financial Servicesmentioning
confidence: 99%
“…As a novelty, we bring the sustainability dimension into this relationship. In this journal, scholars in a similar research stream suggested ways on how to mitigate perceived barriers to green consumption processes (Beatson et al , 2020), and they have examined the role of personal and subjective norms influencing pro-environmental behavior (Setiawan et al , 2021); however, none of these studies specifically explored consumers’ desire for the new as a barrier against sustainability in the context of fashion industry. This conceptual study’s original contribution to social marketing studies comes from revealing in detail the challenges and potential downstream and upstream solutions at micro, meso and macro levels for aligning consumers’ restless desire for newness and the pressing need for sustainability.…”
Section: Introductionmentioning
confidence: 99%